Global imperatives, local contingencies: An analysis of divergent priorities and dominant perspectives in stove development from the 1970s to date. (January 2014) - Sesan, Temilade
This article traces the trajectory of cookstove development in the south beginning in the 1970s. Three distinct but overlapping phases of stove development are identified which were initiated in response to various risks identified by 'outsider' northern and multilateral actors to poor households in the south cooking with solid biomass fuels. The article critically examines the objectives and underlying assumptions of each phase and concludes that, despite the rhetorical shift from an expert-led to a context-responsive approach from the 1980s onwards, the priorities and policies of outsider organizations continue to dominate the stove development agenda in the current market-based phase.